METHODOLOGIES’ APPLICATION FOR THE DEVELOPMENT OF TRANSPORT STRATEGY (URBAN PASSENGER TRANSPORT) - E. S. Temnov (Вестник СибАДИ)
Introduction. The paper substantiates the relevance of the development of regional transport strategies, which are basic for the implementation of organizational, technical and economic solutions aimed at the reorganization of modern urban and regional transport systems. Moreover, it is indicated that the development of strategies should be accompanied by a comprehensive and coordinated survey and modeling of transport systems, including within the framework of the regional programs of integrated development of transport infrastructure, projects for the creation of integrated traffic management schemes, as well as integrated schemes of transport services to the population. The aim of the research is to formulate the tasks consisting the proposals at the coordination of all the above and other programs that ensure long-term planning, continuity of decisions and budget savings directed to the development of transport in the regions.Materials and methods. Methods of system analysis, theory of transport systems, as well as methods that are widely used in the community of transport engineers, including various options for  calculation and experimental methods of transport planning and modeling of transport systems for the city or agglomeration, are used to solve the research problems.Results. Based on the information synthesis of the stages of regional transport strategies development, a sequence of actions is proposed, leading to the required methodological and organizational approaches, with which it is possible to perform the solution of the  strategic task. The authors formulate a list of major programs that need to be addressed at the level of regional ministries (departments) or departments of transportation municipalities with the goal of implementing transport strategies and aligning them with projects noted above. Discussion and conclusions. The main result of this work is the conclusion about the feasibility of rational actions of regional and municipal transport governing bodies, which could be planned within the framework of regional (municipal) transport strategies. The basis is the application of the proposed methodological and organizational recommendations.